2018
DOI: 10.1371/journal.pone.0205372
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in the development of rat submandibular glands in offspring of diabetic mothers: Biochemical, histological and ultrastructural study

Abstract: Development and maturation of submandibular salivary glands are influenced by intrauterine diabetic environment. Several studies investigated the effects of diabetes on the salivary glands. However, the effects of maternal diabetes on the submandibular glands of the offspring was not properly examined. Therefore, the present study was designed to describe the changes in the development of the submandibular glands of the offspring of diabetic mothers. The submandibular glands of the offspring of Streptozotocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…The light microscopic examination of the parotid glands after diabetic induction in the present study revealed loss of acinar outlines with intracellular vacuolization and the gland begin to regain their symmetrical shape and size after receiving moringa oleifera, these results in agreement with Abir El Sadik et al, 2018 who found in their study after 2 week of diabetic induction that the salivary glands showed damaged effects in acini presented by multiple vacuoles with nucleus displacement while striated ducts presents atrophy and pyknotic nuclei and vacuoles surrounding cells, 18 .…”
Section: Bar Charts Showing Estimated Mean Values Of Comet Assay For supporting
confidence: 92%
See 1 more Smart Citation
“…The light microscopic examination of the parotid glands after diabetic induction in the present study revealed loss of acinar outlines with intracellular vacuolization and the gland begin to regain their symmetrical shape and size after receiving moringa oleifera, these results in agreement with Abir El Sadik et al, 2018 who found in their study after 2 week of diabetic induction that the salivary glands showed damaged effects in acini presented by multiple vacuoles with nucleus displacement while striated ducts presents atrophy and pyknotic nuclei and vacuoles surrounding cells, 18 .…”
Section: Bar Charts Showing Estimated Mean Values Of Comet Assay For supporting
confidence: 92%
“…Degenerated, swollen and irregular cristae of mitochondria. Irregular, dilated and degenerated rough endoplasmic reticula in cytoplasm, 18 .…”
Section: Bar Charts Showing Estimated Mean Values Of Comet Assay For mentioning
confidence: 99%
“…EGF production is impaired by diabetes and it has been invoked as a major factor for wound chronification . Experimentally induced diabetes damages the submandibular salivary glands physiology, accounting for a concomitant reduction of EGF output . Furthermore, reduced levels of salivary EGF in diabetic patients contribute to the development of oral and systemic complications of diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…43 Experimentally induced diabetes damages the submandibular salivary glands physiology, accounting for a concomitant reduction of EGF output. 44 Furthermore, reduced levels of salivary EGF in diabetic patients contribute to the development of oral and systemic complications of diabetes. 45 This theoretical background encouraged us to examine the possible impact of EGF infiltration on its salivary levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although type 1 diabetes in rat and mouse animal models displays reduced saliva production, divergent data exist concerning a modification in AQP5 expression, localization and muscarinic agonist-induced translocation [ 79 , 124 , 125 ]. It is noteworthy that maternal type 1 diabetes induced postnatal changes in the development of rat SG in offspring, including decreased AQP5 expression [ 126 ]. Rats with type 2 diabetes displayed decreased saliva flow, inflammatory cell infiltration of SG and decreased AQP5 expression [ 127 ].…”
Section: Involvement Of Aqps In Sg Pathologiesmentioning
confidence: 99%